Changes in Knowledge and Compliance with Pitch Count Recommendations Among Youth Baseball Coaches: A Cross-Sectional Comparison at Two Time Points - Makita M; Onishi M; Kouno C; Kawabe R; Doi N; Tahu Y; Aoyama T; Nagai-Tanima M (Open Access Journal of Sports Medicine, 2025)
Mona Makita,1,* Miyu Onishi,1,* Chika Kouno,1 Rika Kawabe,1 Naoki Doi,1 Yukinobu Tahu,2 Tomoki Aoyama,1 Momoko Nagai-Tanima1 1Department of Human Health Science, Graduate School of Medicine, Kyoto University, Kyoto, Japan; 2Kyoto Prefecture Sports Little League Baseball Association, Kyoto, Japan*These authors contributed equally to this workCorrespondence: Momoko Nagai-Tanima, Human Health Science, Graduate School of Medicine, Kyoto University, 53 Kawahara-cho, Shogoin, Sakyo-ku, Kyoto, 606-8507, Japan, Tel +81 75 751 3964, Email tanima.momoko.8s@kyoto-u.ac.jpBackground: In Japan, pitch count recommendations were proposed to prevent throwing injuries. In our laboratory, 10 years ago, the knowledge and compliance with pitch count recommendations were assessed among coaches in Kyoto Prefecture and compared with those in the US Since then, the youth baseball environment has changed, including the formal implementation of pitch count rules by the Japan Boys League Foundation. However, no studies have examined how such changes have influenced coaches’ knowledge and compliance over time. Although it is important for coaches to have prior knowledge of injuries in order to prevent the incidence of Little League Elbow, few studies have assessed the actual experience of coaches.Methods: Of the 242 coaches belonging to the Kyoto Boys’ Baseball Association who participated, 172 with valid responses were analyzed. The questionnaire, consistent with a previous study conducted 10 years ago, assessed knowledge and compliance with pitch count recommendations, as well as coaching background and seminar participation.Results: The proportion of coaches who reported having knowledge of the recommendations significantly increased from 39.8% to 52.3% (p = 0.04), while the compliance rate decreased from 28.3% to 22.1% (p = 0.23). Coaches with knowledge tended to be older and have longer coaching experience, while those who complied were significantly younger and less experienced. Seminar participation was associated with increased knowledge but did not result in higher compliance. Moreover, 70% of coaches were also parents of players; these individuals were younger, had less coaching experience, and were less likely to have attended seminars.Conclusion: Despite increased knowledge among youth baseball coaches, compliance with pitch count recommendations remains limited. This knowledge–behavior gap suggests the need for educational interventions that address not only the dissemination of information but also cultural and psychological barriers to behavior change. Tailored support may be especially beneficial for younger and less experienced coaches.Keywords: Little League, coaches, pitch count recommendation, elbow pain